Lifestyle Construction in Coffee Shops in Malang City from the Perspective of Symbolic Violence - Marlina, Baiq Nana (Kanal: Jurnal Ilmu Komunikasi, 2024)
The coffee shop industry is experiencing rapid growth as coffee consumption increases in Indonesia. The focus of this research is Malang City, which is the center of coffee shop growth in Indonesia. Through a cultural studies paradigm approach, this research aims to understand the construction process of coffee consumer lifestyles in Malang City. This phenomenon marks a shift in consumer behavior from necessity to a sub-culture where coffee shops are not only a gathering place, but also a symbol of self-identity and an urban lifestyle. The research used visual methods with 6 participants from two different coffee shops. The data collection process focused on coffee shops, interior design, consumers, and visual elements that influence lifestyle. The concept of Pierre Bourdieu's social praxis theory is used as an analytical framework to understand the construction of lifestyle and the role of symbolic power. The research results show that the existence of coffee shops influences culture and lifestyle in Malang City. Starbucks, as the main agent, shapes the values and standards adopted by local coffee shops such as Amstirdam. Patterns of symbolic violence emerge in consumer clothing standards, depicting coffee shops not only as places to buy and sell coffee, but also as public spaces that shape identity and social norms. This research contributes to a deeper understanding of the role of coffee shops in shaping lifestyle and culture in society.